Računalniško podprta karakterizacija termo-reoloških lastnosti snovi - Koc, Pino (Kovine zlitine tehnologije, 1997)
Successful treating of technical problems by means of numerical analysis and computer simulation is conditioned by a good knowledge of the material properties that characterize the considered problem. The computer aided identification of the temperature dependent rheological material properties, which is based on the inverse problem solution methodology, is presented in the paper.
Keywords: lastnosti snovi; modeliranje matematično; problemi inverzni; karakterizacije materialov; karakterizacija CA; reologija; računalniška simulacija; temperatura; mehanske lastnosti